2009
DOI: 10.1590/s1516-18462009005000060
|View full text |Cite
|
Sign up to set email alerts
|

Eficácia terapêutica do programa de remediação fonológica em escolares com dislexia do desenvolvimento

Abstract: , Ian Smythe (7) RESUMO Objetivos: comparar os achados da avaliação em situação de pré e pós-testagem em escolares com dislexia do desenvolvimento e escolares bons leitores submetidos ao programa de remediação fonológica e veri car a e cácia terapêutica do programa de remediação fonológica em escolares com dislexia do desenvolvimento. Métodos: participaram deste estudo 40 escolares de 2ª a 4ª série de ensino público do município de Marília-SP, de ambos os sexos, na faixa etária de 8 a 12 anos distribuídos em: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0
6

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 25 publications
1
9
0
6
Order By: Relevance
“…This fact corroborates the findings of other studies which show that school children diagnosed or at risk for reading difficulties not submitted to interventions did not present spontaneous improvement of reading and writing skills (11,27) . Nevertheless, the phonological and writing working memory skills were not directly stimulated by the intervention program used, considering that strategies were not used with the aim of training these abilities during the sessions; even so, the children of the SG had these skills improved.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This fact corroborates the findings of other studies which show that school children diagnosed or at risk for reading difficulties not submitted to interventions did not present spontaneous improvement of reading and writing skills (11,27) . Nevertheless, the phonological and writing working memory skills were not directly stimulated by the intervention program used, considering that strategies were not used with the aim of training these abilities during the sessions; even so, the children of the SG had these skills improved.…”
Section: Discussionsupporting
confidence: 92%
“…As a rule, these programs comprise 18 to 24 sessions (7)(8)(9)(10)(11)(12) . In recent years, based on systematic literature reviews, some authors (13) have found a considerable number of studies addressing intervention programs for children at risk for dyslexia in the international literature; in contrast, a much smaller number of publications has been found in the Brazilian literature, thus demonstrating the importance to conduct research involving intervention programs focusing on school children at risk for this disorder.…”
Section: Introductionmentioning
confidence: 99%
“…In the area of reading and writing, we find in the national literature research related to early intervention programs with children in elementary education at risk for dyslexia (5,6) . Based on the cognitive theory, they look for factors that indicate that the child presents a risk for dyslexia by evaluating for phonological abilities and the letter-sound correspondences.…”
Section: Introductionmentioning
confidence: 98%
“…Na literatura nacional [30][31][32][33][34][35] , os estudos enfocam o desenvolvimento de programas com base fonológica e leitura com escolares já diagnosticados com dislexia ou distúrbio de aprendizagem.…”
Section: Introductionunclassified